Sistem Pemesanan Tiket Pesawat dengan Menggunakan J2ME - Chusnul Chotimah, Wawan Laksito, Muhammad Hasbi (STMIK Sinar Nusantara, 2012)
One example of this technology is the use of flight bookings through mobile devices, also known as the M-Ticketing. With the M-Ticketing can facilitate modern society who have little time to buy or book air tickets directly to airline ticket agents. M-Ticketing allows people to book tickets anywhere, anytime using mobile devices connected to the Internet networkKeywords: M-Ticketing, J2ME